On certain finite series involving the H-function of two variables - Gupta, K. C.; Garg, O. P. (Revista Técnica da Faculdade de Engenharia da de Zulia)
In this paper we obtain two new and interesting finite series for the H- functions of two variables in a very elegant form and without having severe restrictions on the parameters involved by a direct and simple method. On account of the most general nature of the H-function of two variables, a number of related finite series for a number of other simple and useful functions can also be obtained as special cases of our results. As an illustration, we obtain here from our main results, the corresponding finite series for Kampé de Fériet function, Apell”™s functions and Gauss’ hypergeometric function which are also believed to be new . Thus the present study provides us a number of interesting new results for a large spectrum of special functions in a direct and simple manner.